STUDI ETNOGRAFI KOMUNIKASI PADA MASYARAKAT KENAGARIAN TALAWI (STUDI PADA “KATO NAN AMPEK”) - Mutia Rahayu; Tessa Shasrini (Jurnal Ranah Komunikasi, 2022)
This study was conducted to determine the use of Kato nan Ampek in the Kenagarian Talawi community in communicating based on ethnographic studies. This research was conducted to describe, analyze and find out how communication is carried out using Kato nan Ampek in the Kenagarian Talawi community. This study uses an understanding of qualitative methods, where this method aims to explain a socio-cultural phenomenon from ethnographic studies and participant perspectives, with data collection techniques that include interviews, field observations and documentation. The data validity technique used triangulation technique. The informants in this study were four people who understood Minangkabau cultural customs, which consisted of the Chairman of the Talawi Density (KAN), the head of the Sumagek ​​and two Talawi youths who understood customs, as well as a high social sense of course they felt the changes in communication. The researcher uses three ethnographic study objects, namely communication activities, communication components and language varieties as the basis for analyzing research. The results of this study indicate that the use of Kato nan Ampek in Kenagarian Talawi is more commonly found in formal communication activities by looking at the participants in the communication component and the varieties of the Talawi regional language itself which is seen from the differences in dialect when communicating.